STRATEGI PENDIDIKAN ISLAM DALAM UPAYA MENJAWAB TANTANGAN GLOBALISASI - Syamsul Aripin (TARBIYA: Journal of Education in Muslim Society, 2014)
Globalization has been affecting many aspects of human life, such as, social, politics, economic, culture, information and communication, and education. The development of technologyy in globalization era has brought society into wider world. Connection among individuals becomes easier. What happen in one part of the world can be instantly accessed by others in other part of the world. Information and knowledge can effortlessly be obtained from various sources of technology, such as, radio, television, internet, newspaper and magazines. This situation brings about consequences on education. Modern schools, crative teachers, high performance students are among consequences of the development of technology. Islamic schools, as part of schools, should be able to respond this situation in order not to be left behind. While some efforts might be taken to improve the quality of Islamic educational institutions, such as improving learning quality, preparing competitive graduates both from Islamic boarding schools (pesantren) and Islamic schools (madrasah), pesantren and madrasah are encouraged to preserve their characteristics that have existed for years. DOI: 10.15408/tjems.v1i2.1266